Amino Acid Requirements for Nile Tilapia: An Update - Wilson Massamitu Furuya; Thais Pereira da Cruz; Delbert Monroe Gatlin (Animals, 2023)
This review aims to consolidate the relevant published data exploring the amino acid (AA) requirements of Nile tilapia, Oreochromis niloticus, and to reach a new set of recommendations based on those data. There are still inconsistencies in lysine, sulfur-containing AA, threonine, tryptophan, branched-chain AA, and total aromatic AA recommendations in data that have appeared since 1988. This review finds that strain, size, basal diet composition, and assessment method may have contributed to the inconsistencies in AA recommendations. Currently, the expansion of precision AA nutrition diets for Nile tilapia is receiving more attention because of the demand for flexibility in widespread ingredient substitutions which will allow compliance with environmentally sustainable principles. Such approaches involve changes in diet ingredient composition with possible inclusions of non-bound essential and non-essential AAs. Increasing the inclusion of non-bound AAs into Nile tilapia diets may modify protein dynamics and influence AA requirements. Emerging evidence indicates that not only essential but also some non-essential amino acids regulate growth performance, fillet yield, and flesh quality, as well as reproductive performance, gut morphology, intestinal microbiota, and immune responses. Thus, this review considers current AA recommendations for Nile tilapia and proposes refinements that may better serve the needs of the tilapia industry.